Implementasi Program Rehabilitasi Sosial Dalam Penanggulangan Gelandangan Dan Pengemis Di Kabupaten Karangasem - Ni Kadek Nina Perianti; Lilik Antarini; Komang Ema Marsita Dewi (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2025)
This research is motivated by the rampant cases of vagrants and beggars spread across several areas in major cities in Bali such as traffic lights, coasts and shopping centers. This study is intended to analyze the Implementation of the Social Rehabilitation Program for homeless people and beggars in Karangasem Regency. The theory used in this study is the theory of Policy Implementation according to Van Meter and Van Horn. Several factors that can determine the success of a policy implementation are standards and objectives, resources, characteristics of the implementing organization, communication between related organizations and implementing activities, attitudes of implementers, and conditions of the social, economic, and political environment. The research method used is a qualitative research method with a descriptive approach. The data collection technique uses three methods, namely interviews, observations, and documentation. The data that has been collected is analyzed starting from data reduction, then data presentation, and finally conclusion drawn. The research was carried out at the Karangasem Regency Social Service. The results of the study show that the implementation of the social rehabilitation program for gepeng has been carried out, but there are several variables that have not been fulfilled and there are obstacles that make it difficult to implement the program. Then it is also hoped that the Karangasem Regency Social Service and local Traditional Villages will cooperate in verifying the identity of homeless people and beggars so that there is no change in identity to facilitate the distribution of aid. To overcome social stigma, it is necessary to involve social experts or psychologists and conduct socialization to the community. The Social Rehabilitation Program must be a priority program with adequate budget and resources